The Fish Pathogen Yersinia ruckeri Produces Holomycin and Uses an RNA Methyltransferase for Self-resistance - Qin, Zhiwei (American Society for Biochemistry and Molecular Biology, 2013)
Holomycin and its derivatives belong to a class of broad-spectrum antibacterial natural products containing a rare dithiolopyrrolone heterobicyclic scaffold. The antibacterial mechanism of dithiolopyrrolone compounds has been attributed to the inhibition of bacterial RNA polymerase activities, although the exact mode of action has not been established in vitro. Some dithiopyrrolone derivatives display potent anticancer activities. Recently the biosynthetic gene cluster of holomycin has been identified and characterized in Streptomyces clavuligerus. Here we report that the fish pathogen Yersinia ruckeri is a holomycin producer, as evidenced through genome mining, chemical isolation, and structural elucidation as well as genetic manipulation. We also identified a unique regulatory gene hom15 at one end of the gene cluster encoding a cold-shock-like protein that likely regulates the production of holomycin in low cultivation temperatures. Inactivation of hom15 resulted in a significant loss of holomycin production. Finally, gene disruption of an RNA methyltransferase gene hom12 resulted in the sensitivity of the mutant toward holomycin. A complementation experiment of hom12 restored the resistance against holomycin. Although the wild-type Escherichia coli BL21(DE3) Gold is susceptible to holomycin, the mutant harboring hom12 showed tolerance toward holomycin. High resolution liquid chromatography (LC)-ESI/MS analysis of digested RNA fragments demonstrated that the wild-type Y. ruckeri and E. coli harboring hom12 contain a methylated RNA fragment, whereas the mutated Y. ruckeri and the wild-type E. coli only contain normal non-methylated RNA fragments. Taken together, our results strongly suggest that this putative RNA methyltransferase Hom12 is the self-resistance protein that methylates the RNA of Y. ruckeri to reduce the cytotoxic effect of holomycin during holomycin production.